Pengembangan Media Pembelajaran Berbasis Video Tutorial Interaktif Pada Mata Pelajaran - Baiq Ade Irma Williyana; Yosi Nur Kholisho; Ahmad Fathoni (Universitas Hamzanwadi, 2018)
This research aims to: (1) developing video-based learning media is an interactive tutorial on subjects of engineering animation 2 dimensions with frame animation technique material class XI Multimedia at SMK Negeri 1 Kopang (2) know the feasibility of media interactive video tutorial-based learning. This type of research is a Research and Development (RD) and the development of procedures: potential and problems, data collection, product design, design validation, product test design, revision, revision products, free trial usage. The software development model used the waterfall model. The feasibility study is judged by media experts, media content and users. Data collection instruments namely documentation and questionnaires. Data analysis the results of the test the feasibility of using the Likert scale. Results of research: (1) media video-based learning, interactive tutorials that were developed in the form of software packaged in the form of an .exe file and interactive CD. (2) a Media-based learning video tutorials worth used in the learning process, based on the results of the validation of media experts earn a percentage of 86.69%, expert of 82.81%, material and product testing of 75.93% and trial usage earn a percentage of 79.89%. Overall the media-based learning, interactive video tutorial earn a percentage of 76.66% eligibility category in the media